How are Australian higher education institutions contributing to change through innovative teaching and learning in virtual worlds? - Gregory, B.; Gregory, S.; Wood, D.; Masters, Y.; Hillier, M.; Stokes-Thompson, F.; Bogdanovych, A.; Butler, D.; Hay, L.; Jegathesan, J.; Flintoff, Kim; Schutt, S.; et al. (University of Tasmania, 2011)
Over the past decade, teaching and learning in virtual worlds has been at the forefront of many higher education institutions around the world. The DEHub Virtual Worlds Working Group (VWWG) consisting of Australian and New Zealand higher education academics was formed in 2009. These educators are investigating the role that virtual worlds play in the future of education and actively changing the direction of their own teaching practice and curricula. 47 academics reporting on 28 Australian higher education institutions present an overview of how they have changed directions through the effective use of virtual worlds for diverse teaching and learning activities such as business scenarios and virtual excursions, role-play simulations, experimentation and language development. The case studies offer insights into the ways in which institutions are continuing to change directions in their teaching to meet changing demands for innovative teaching, learning and research in virtual worlds. This paper highlights the ways in which the authors are using virtual worlds to create opportunities for rich, immersive and authentic activities that would be difficult or not possible to achieve through more traditional approaches.